2008
DOI: 10.1016/j.joca.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Joint space narrowing and Kellgren–Lawrence progression in knee osteoarthritis: an analytic literature synthesis

Abstract: While radiographic approach and study design were associated with JSN, OA definition, cohort composition and study duration were associated with risk of K-L progression. These findings may inform the design of disease modifying osteoarthritis drug (DMOAD) trials and assist clinicians in optimal timing of OA treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
4
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 41 publications
6
112
4
3
Order By: Relevance
“…In particular, BMI is usually considered a risk factor of incident OA. However, the association between mean BMI and JSL was not found in a recent review (26). Our results are in contrast with studies showing a positive association between increased urinary CTX-II levels and progression of knee (33) or hip (34) OA, but are consistent with a study by Mazzuca et al, who found no relationship between urinary CTX-II and JSL (35).…”
Section: Knee Joint Space Study In Womensupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, BMI is usually considered a risk factor of incident OA. However, the association between mean BMI and JSL was not found in a recent review (26). Our results are in contrast with studies showing a positive association between increased urinary CTX-II levels and progression of knee (33) or hip (34) OA, but are consistent with a study by Mazzuca et al, who found no relationship between urinary CTX-II and JSL (35).…”
Section: Knee Joint Space Study In Womensupporting
confidence: 76%
“…Most of the previous studies were performed in patients with knee OA defined by a K/L scale score Ն2 (26). One longitudinal study assessed JSL in knees without radiographic OA in elderly men and women (ages 70 -79 years) with knee pain (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Günther and Sun [13] described inferior interobserver intraclass correlation coefficients for medial compartment (0.62) and lateral compartment (0.47) JSN as well as medial femorotibial, lateral femorotibial, and tibial spine osteophyte formation (0.75, 0.74, and 0.63, respectively) as compared with the overall KL classification score (0.81) when using three observers, one of whom was an experienced orthopaedic surgeon and two of whom were orthopaedic residents. As discussed by Emrani et al [8], classifications based on JSN may be preferable to the KL system for monitoring progression of OA, whereas the KL system may be better for assessing severity of osteoarthritic disease. A criticism of multiple classification systems (including the KL) is the lack of recognition of patellofemoral arthritis as a distinct or contributory radiographic factor.…”
Section: Limitationsmentioning
confidence: 99%
“…Twenty years later, among those classified as having milder disease (defined as Albäck class I: Ն50% JSN at study entry; n ϭ 47), 39% showed no radiographic progression (18). A 2008 systematic review of 27 observational and randomized controlled trial (RCT) studies of knee OA JSN concluded that estimates ranged from Ϫ0.10 mm/year (indicating an increase in JSW over time) to 0.70 mm/year, with a mean Ϯ SD loss of 0.13 Ϯ 0.15 mm/year (19). In the original parent study for our analysis, radiographic progression of the entire group was only 0.088 mm over 2 years in the European cohort and 0.13 mm in the North American cohort, which was significantly less than an anticipated rate of 0.20 mm per year.…”
Section: (3)mentioning
confidence: 99%